Ultrastructure distribution of microcystin-LR and its migration mechanism by nanoanalytical investigation. (October 2022) - Liu, Shuyu; Xiao, Jiali; Min, Xin; Tan, Yan; Ma, Fang; Liu, Li
Abstract: The resonance spectrum system established by gold nanorods was used for analyzing the production process of MC-LR(Microcystin-LR) to explain the distribution, binding mode, and migration process of MC-LR in different microstructures during the growth of microalgae. The accuracy of the nanoanalytical system was verified by combining with the MC-LR standard curve detected by liquid chromatography/mass spectrometry at the concentration of 0.5–8000 nM. Comparing the concentration of MC-LR extracted from different microstructures of microalgae by modified gold nanorods with by LC-MS during the complete growth cycle, the average recovery was 95.6%–101.6%, with error less than 10%. Based on this nano-system investigation, it was found that MC-LR migrated from thylakoid membrane to phycobiliprotein and then to the outer membrane and cell wall through the early growth to stable phase. The -COOH group in Glu combined with -CH in uranic acid, Me-Asp structure in MC-LR combined with -NH in protein, and = N-CH3 in the Mdha structure combined with -OH in polysaccharide, respectively. Graphical Abstract: ga1 Highlights: MC-LR migrated from thylakoid membrane to phycobiliprotein, then the outer membrane. -COOH in Glu, Me-Asp structure, N-CH3 in the Mdha combined with -CH, -NH. Deeply analysis ultrastructural localization and migration of intracellular MC-LR.